THE EFFORTS TO IMPROVE FINANCIAL PERFORMANCE AND MANAGERIAL PERFORMANCE THROUGH PARTICIPATIVE BUDGETING AND BUDGETARY CONTROL - Pangaribuan, Hisar; Pangaribuan, Bonar Alberto; Siagian, Harlyn L. (Distribusi - Journal of Management and Business, 2024)
This study examines how participative budgeting and budget control can improve a company's financial and managerial performance. The research method used is quantitative confirmation with a variance-based approach. Questionnaires were distributed online to respondents involved in the budgeting process in order to collect data and facilitate their objective perception of the variables under study. There were 67 respondents who filled out the questionnaire completely and processed it validly. The data's validity and reliability are confirmed by meeting the necessary criteria for processing, including the loading factor, average variance extracted, composite reliability, and discriminant validity with a heterotrait-monotrait ratio. The study results have shown that adequate budget control and involvement of related parties in making budgets will increase discipline and a good understanding of budgets for managers so that they can significantly improve the company's managerial and financial performance.